THE RELATIONSHIP OF PERSONAL FACTORS AND FAMILY SUPPORT WITH SELF MANAGEMENT OF TYPE II DIABETES MELLITUS PATIENTS AINON PEMATANGSIANTAR CLINIC - Nurmala; Rina Valensi; Novita Sinaga (RADJA PUBLIKA, 2023)
Based on data from the International Diabetes Federation in 2014, it was found that type 2 diabetes sufferers are increasing every year in every country and by 2035 it is estimated that diabetes sufferers will increase to 592 million people, and Indonesia is in 7th place. Diabetes is a degenerative disease that occurs for life. Diabetics will experience difficult times due to changes in themselves, so they need support from those around them, especially family support to help them control their lifestyle and self-management care for families with diabetes. Diabetes is a chronic disease that requires diabetes self-management to prevent serious complications. This study aims to identify the relationship between family support and self-management of people with diabetes mellitus at the Ainon Pematangsiantar Clinic. The design in this study used a quantitative approach to cross sectional design with a sample of 35 respondents. Data analysis used the Chi Square test. The results showed that there was no significant relationship between family support and diabetes self-management (p value = 0.274 at a = 0.05). Researchers suggest the need for dissemination of information related to self-management through counseling and also the need for home visits for those who cannot attend the Ainon Clinic due to physical conditions that do not allow it.